Energy Simulations of a Building Insulated with a Hemp-Lime Composite with Different Wall and Node Variants - Przemysław Brzyski; Magdalena Grudzińska; Martin Böhm; Grzegorz Łagód (Energies, 2022)
Thermal bridges constitute a significant share in the overall heat losses through building partitions. This is an important issue not only in traditional but also ecological buildings, where the load-bearing structure is often a wooden frame. In partitions insulated with hemp-lime composite, the skeleton is usually hidden in the insulation. However, in some nodes or jambs, wooden elements may be exposed or have a large cross-section, intensifying the heat transfer. This work presents simulations of energy demand in a single-family building insulated with hemp-lime composite, using the BSim dynamic simulation program. The calculations take into account the linear thermal transmittance of structural nodes modeled in the THERM program. The energy demand for heating and the share of thermal bridges in the heat loss of the entire building were calculated for different locations of the structural framework in the walls, as well as the size and number of windows. The share of thermal bridges in heat losses was about 10%, and the differences in energy demand for heating using various frame locations in the wall were negligible.